Compactification of Friedmann's hyperbolic model - Fagundes, Helio V. (American Physical Society (APS), 1983)
A compact hyperbolic three-manifold is substituted for the infinite space H3, as space section of Friedmann's cosmological model of negative curvature. Some consequences are briefly analyzed. In particular it is shown that an apparent observational isotropy persists when the particle horizon intersects an anisotropic region of space. © 1983 The American Physical Society.